Pengaruh Financial Attitude,Financial Knowledge, Parental Income Terhadap Financial Management Behavior - Irine Herdjiono; Lady Angela Damanik (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
The aim of this research is to obtain the knowledge regarding the influence of Financial Attitude, Financial Knowledge, and Parental Income toward Financial Management Behavior. This research conducted in Merauke, border area of Indonesia. Questionnaire is used to collect the data.The sample 382 respondents. Correspondence analysis and chi-square are used to analyze.The result of this research show that Financial Attitude has influence toward Financial Management Behavior while Financial Knowledge and Parental Income have no influence toward Financial Management Behavior.This research has two implications, (1) attitude is an important factor in supporting financial behavior, where the attitude is generally influenced by environment and social interaction and (2) the financial knowledge has no influence on the financial behavior because financial education is less effective in low-medium income countries or regions.